(untitled) (La U Investiga, 2024)
Complicated urinary tract infection (cUTI) is a common cause of hospitalization globally. There are cUTI management protocols tailored to the specific epidemiology of each hospital setting, as supported by the local focus of this study. Objective: To describe the etiological agents, sensitivity profile and antimicrobial resistance of complicated urinary tract infection in patients admitted to the internal medicine service. Methodology: A cross-sectional, observational and descriptive study was carried out on patients over 18 years of age hospitalized in the Internal Medicine Service, with a total of 138 participants. Pregnant women were excluded and patients with medical histories and records of urine cultures documented at the health institution were included. Results: During the study period, 112 cases of cUTI with positive urine cultures were identified. The most prevalent microorganisms were Escherichia coli (84.8%), followed by Klebsiella pneumoniae (8%), Proteus mirabilis (4.5%) and Pseudomonas aeruginosa (2.7%). These four microorganisms showed high sensitivity to amikacin, meropenem, fosfomycin and nitrofurantoin. However, they exhibited significant resistance to Sulfatrimethoprim (48.4%), Ampicillin (47.4%), and Ciprofloxacin (46.3%). In addition, high resistance will be observed to first and second generation cephalosporins, as well as ampicillin. Conclusions: This study highlights that in patients over 18 years of age hospitalized with cUTI, Escherichia coli is the most commonly isolated microorganism. In addition, a worrying resistance to quinolones is evident. These results underline the importance of an effective cUTI management strategy in hospital settings, taking into account antimicrobial resistance.